Rhinovirus infection presenting with symptomatic hyponatremia—Atypical presentation of a common infection - Koutaibah Obaid (21768293) (2024)
Key Clinical Message Rhinovirus infection has the potential to exhibit unconventional symptoms like symptomatic hyponatremia. Health care professionals should remain vigilant about this potential complication, especially in cases with uncommon presentations. Timely identification and effective management of hyponatremia can mitigate potential complications and enhance patient prognosis. The syndrome of inappropriate secretion of antidiuretic hormone (SIADH) is a prominent contributor to low sodium levels. Various factors can contribute to hyponatremia, affecting the diagnosis and treatment of the condition. Of note, some infections have been identified as potential causes of SIADH. Although rhinovirus infection has been linked to SIADH, it is usually associated with severe respiratory infections. Herein, we present a distinctive case where rhinovirus caused significant hyponatremia symptoms, even in the absence of typical respiratory symptoms or fever. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.8773